1995
DOI: 10.1093/infdis/171.3.537
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Nevirapine: Safety, Pharmacokinetics, And Antiviral Effect In Patients With Human Immunodeficiency Virus Infection

Abstract: Nevirapine, a potent nonnucleoside reverse transcriptase inhibitor, produces a transient antiviral effect at < or = 200 mg/day due to the selection of resistant virus. To examine if higher levels of nevirapine could produce sustained antiviral activity, its safety, pharmacokinetics, and antiviral activity at 400 mg/day were studied in 21 patients. There was a rapid reduction in immune complex-dissociated p24 antigen and serum human immunodeficiency virus RNA concentration in all patients, and 8 of 10 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
123
2
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(137 citation statements)
references
References 20 publications
9
123
2
3
Order By: Relevance
“…In our study, as with most other authors [10]- [13], anti-infectious sulfonamides were the most frequently involved drugs. They were followed by the antiretrovirals and quinine.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study, as with most other authors [10]- [13], anti-infectious sulfonamides were the most frequently involved drugs. They were followed by the antiretrovirals and quinine.…”
Section: Discussionsupporting
confidence: 88%
“…Antiretroviral (nevirapine) occupied the second place in our study. Nevirapine is known as a major provider of drug eruptions, and several studies have documented the high incidence of drug reactions induced by nevirapine and their severity [13]- [17]. In opposite, in the series of Pitche et al in Togo [11] and Mame Thierno et al in Senegal [5], antiretroviral drugs have not been found, which can be due to the fact that in Togo, despite the high prevalence of HIV infection no HIV-infected patients in this country was on antiretroviral treatment (for economic reasons, the majority of HIV-infected patients did not yet have access to antiretroviral drugs in Africa) [11].…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17] C max = peak concentration; C min = trough concentration; T max = Time to attain C max ; AUC = area under the plasma concentration versus time curve; t ½ = half-life; BMI = body mass index. fact that Indian patients weigh less than Europeans and Americans and that nevirapine clearance is dependent on body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Since the occurrence of HAART, there is an additional risk of cutaneous toxicity associated with some of these drugs [5][6][7], mainly nevirapine. Indeed, several studies have documented the high incidence of drug-induced dermatitis induced by nevirapine [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies have documented the high incidence of drug-induced dermatitis induced by nevirapine [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%